Nepheline syenite magma differentiation with continental crustal assimilation for the Cabo Frio Island intrusive complex, State of Rio de Janeiro, Brazil - Motoki, A.; Araújo, A.; Sichel, S.; Geraldes, M.; Jourdan, Fred; Motoki, K.; Da Silva, S. (2013)
This article presents chemical composition and magma differentiation process of the alkaline rocks of the Cabo Frio Island and the adjacent areas, State of Rio de Janeiro, Brazil, with special attention to continental crust assimilation. The intrusive body is made up mainly of nepheline syenite, alkaline syenite, and trachyte. The country orthogneiss is intruded also by subvolcanic vent breccia, as well as by lamprophyre, trachyte, and phonolite dykes. The alkaline syenite is distributed at the contact zone in which abundant digested host rock xenoliths are present. Most of the nepheline syenite and phonolite samples are highly silica undersaturated with moderate proportion of (Na+K)/Almol. and K2O/(Na2O+K2O)wt%, being classified to be potassic nepheline syenite. The 40Ar-39Ar age for the nepheline syenite is 54.83±0.35 Ma. The variation diagrams indicate fractionation crystallisation of titanite, ilmenite, apatite, and clinopyroxene during the magma cooling of the intrusive body. The nepheline syenite and phonolite are originated from highly differentiated magmas whose compositions are close to the terminal point of the silica undersaturated field. Continental crust assimilation is remarkable. Some alkaline syenite and trachyte samples are constituted by about 50% of the wall rock materials. The continental crust assimilation took place at the last phase of fractionation crystallisation of the nepheline syenite magma. This composition is thermodynamically instable and it could be originated from super-reheating or rapid fluid content elevation caused by new magma injection into the magma chamber.